The Transformation of an Education Institute in Modern Lithuania - Trakšelys, Kęstutis (Pedagogika, 2013)
The modernity theories of western-type societies are understood as a process, when a developing society approaches developed societies, reaching a certain level of economic growth, a certain level of public participation or a certain phase of democratic development, giving access for more individuals to the physical, social and economic mobility. In modern societies, the educational institution has become one of the key factors to ensure the stimulating and securing mobility of individuals. The modern world gives the education prominence in modern societies. Education has become a major means to climb up the ladder of social classes. Therefore, education has to be compulsory so that it prevents people from creating social groups that could turn into ones non - integral, excluded from society. The aim of modern society is to provide equal opportunities to everyone to learn and meet the needs of the times. According to the modernity theory the Institution of Education should become the basis of social security protecting the individual from various social risks in the future. According to functionalists, each social element of a society as a whole, including the educational institution, contributes to the stability of society. Summarizing various descriptions of the concepts of a social institution in the literature one can conclude that social institution is organized associations of people, who perform certain socially important functions through their social roles, or have common goals, values, norms and behavior patterns. Social institutions can be strong or weak, regardless of people‘s trust in them, nor the requirements of social life. It has been noted that in the scientific literature usually four major social institutions are identified: family, education, religion and politics. The importance of the institutions in society depends upon the times, the country’s political and economic context. The process of Institution-building in social life, acquisition of the well-established values is known as institutionalization. It takes place at all levels of social life, in small groups and large organizations. A greater part of ordinary societal life occurs in specialized institutional situations. Today’s social institutions are quite independent, though they are connected by people, who link themselves to a number of social institutions. Social institutions often compete among each other, for each of them aims at managing the main social functions of society. Family, education, church, and government often compete amid each other openly attempting to influence various groups of society.